(untitled) (Eurasian Research Bulletin, 2023)
The article examines the metaphorical and figurative component of the concept of "duty" in the texts of world literature. The concept of "duty" denoting the moral standard is thought about through figurative combinations. In the semantic description of the linguistic and cultural concept, three components are distinguished. As a means of linguistic representation of the concept, a set of synonyms is expressed through words.